PENERAPAN ALGORITMA LINEAR SEARCH DI APLIKASI SECONDHAND - Agustin, Nely Dwi; Cobantoro, Adi Fajaryanto; Setyawan, Mohammad Bhanu; Nurfitri, Khoiru (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2023)
Inflation in Indonesia has been increasing year by year. The high inflation rate has an impact on the increasing production costs of finished goods, resulting in higher prices which this is not balanced by good sales of new products. This has led to a plan to create a secondhand e-commerce platform. This research aims to implement a search feature that facilitates the search for used goods based on keywords. The implementation process involves the use of the Linear/Sequential Search algorithm in the JavaScript programming language and PostgreSQL as the data storage used. In practice, when the keyword matches the data in the database, the search results will be displayed. If there is no data match, the search will not find any relevant products. The result of this research is the availability of the SecondHand application, with a search feature using the Linear/Sequential Search algorithm, which helps facilitate the interaction between sellers and buyers. The results of white box and postman/grey box testing show that the search feature and its functions work well, producing valid outputs, and have a short execution time of around 613.5 ms or 0.6135 seconds based on the results of five tests.Keywords : Linear/Sequential Search Algorithm, Used Goods, SecondHand.